Endodontics : principles and practice - Torabinejad, Mahmoud; Fouad, Ashraf F.; Shabahang, Shahrokh (London : Elsevier, 2021)
From renowned endodontics experts Mahmoud Torabinejad, Ashraf Fouad, and Shahrokh Shabahang comes Endodontics: Principles and Practice, 6th Edition. This focused and extensively revised new edition contains all the clinically-relevant information needed to incorporate endodontics into general dentistry practice. Illustrated step-by-step guidelines and vivid online videos address the ins and outs of diagnosis, treatment planning, managing pulpal and periapical diseases, and performing basic root canal treatments. Updated evidence-based coverage also includes topics such as the etiology of disease, local anesthesia, emergency treatment, obturation, and temporization. It's the perfect endodontics guide for both entry-level dental students and general dentists alike. Well-known, international contributors share guidelines, expertise, and their clinical experience with contemporary technologies and procedures. Authoritative, visually detailed coverage provides a practical understanding of basic endodontic principles and procedures, including pulpal and periapical diseases and their management. Clinically-relevant organization reflects the order in which procedures are performed in clinical settings, enhancing your understanding of the etiology and treatment of teeth with pulpal and periapical diseases. Over 1,000 full-color illustrations ensure a clear, accurate understanding of procedures, and include radiographs and clinical photographs. Learning objectives help you meet the theoretical and procedural expectations for each chapter. More than 67 video clips located on the companion website demonstrate essential procedures.
Pathogenesis of pulp and periapical diseases -- Systemic health considerations in the endodontic patient and geriatric endodontics -- Endodontic radiology -- Endodontic diagnosis and treatment planning -- Differential diagnosis of pains and radiolucencies of nonpulpal origin -- Endodontic case complexity and working with the specialist -- Endodontic armamentarium -- Local anesthesia -- Endodontic emergencies and therapeutics -- Management of the vital pulp and of immature teeth -- Management of traumatic dental injuries -- Root canal anatomy -- Isolation, endodontic access, and length determination -- Cleaning and shaping -- Obturation and temporization -- Restoration of endodontically treated teeth -- Bleaching discolored nonvital teeth -- Procedural accidents -- Nonsurgical retreatment -- Apical microsurgery -- Adjunctive procedures -- Endodontic treatment outcomes -- Appendices. Summary table of the root numbers of the permanent maxillary teeth -- Summary table of the root canal systems of the permanent maxillary teeth -- Summary table of the root numbers of the permanent mandibular teeth -- Summary table of the root canal systems of the permanent mandibular teeth.
Revised edition of: Endodontics : principles and practice / Mahmoud Torabinejad, Richard E. Walton, Ashraf Fouad. Fifth edition. [2015]
Includes bibliographical references.
Description based on online resource; title from electronic title page (ClinicalKey, viewed on May 21, 2021).
Keywords: Root Canal Therapy; Periapical Diseases; Dental Pulp Diseases